Role of ligands in the formation, phase stabilization, structural and magnetic properties of alpha-Fe2O3 nanoparticles - Joshi, Satyawati S.; Patil, Prajakta R.; Nimase, Madhav S.; Bakare, P. P. (Journal of Nanoparticle Research, 2006)
The electrochemical synthesis of alpha Fe2O3 nanoparticles was performed using quaternary ammonium salts viz. TPAB, TBAB and TOAB in an organic medium by optimizing current density and molar concentration of the ligand. The role of ligands in the formation of alpha phase, structure and magnetic properties was investigated in details. The effect of increasing chain length on the particle size confirmed that as the chain length increases from propyl to octyl, the particle size decreases. X-ray diffraction spectra of as prepared samples and TEM analysis confirmed the amorphous nature of iron oxide. TEM showed beads of iron oxide joined together with a size distribution in the range of 6-30 nm. The Mossbauer studies also support this observation that for the lowest particle size, the line width is broader which successively reduces with increase in particle size. Iron oxide capped with TOAB indicated superparamagnetic nature at room temperature. The resultant internal magnetic field of 506 mm/s due to hyperfine splitting clearly established the formation of alpha-Fe2O3 The infrared spectroscopy and pH measurements revealed the binding of tetra alkyl ligand with iron oxide. The IR spectra and the increase in basicity of as prepared samples confirmed the formation of hydrated iron oxide. Above 800 degrees C the spectra indicated only iron oxide. Surface area obtained by BET method was 205 m(2)/g.
Keywords: Alkyl chain length; alpha-Fe2O3; Electrochemistry; magnetic properties; Nanoparticles; narrow size distribution

Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity